Protocols for the Evaluation of Neurodevelopmental Alterations in Rabbit Models In Vitro and In Vivo - Pla, Laura; Kühne, Britta Anna; Guardia-Escote, Laia; Vázquez-Aristizabal, Paula; Loreiro, Carla; Flick, Burkhard; Gratacós, Eduard; Barenys, Marta; Illa, Miriam (Frontiers in Toxicology, 2022)
The rabbit model is gaining importance in the field of neurodevelopmental evaluation due to its higher similarity to humans in terms of brain development and maturation than rodents. In this publication, we detail 14 protocols covering toxicological relevant endpoints for the assessment of neurodevelopmental adverse effects in the rabbit species. These protocols include both in vitro and in vivo techniques, which also cover different evaluation time-points, the neonatal period and long-term examinations at postnatal day (PND) 50-70. Specifically, the protocols (P) included are: neurosphere preparation (GD30/PND0; P2) and neurosphere assay (P3), behavioural ontogeny (PND1; P4), brain obtaining and brain weight measurement at two different ages: PND1 (P5) and PND70 (P12), neurohistopathological evaluations after immersion fixation for neurons, astrocytes, oligodendrocytes and microglia (PND1; P6-9) or perfusion fixation (PND70; P12), motor activity (P11, open field), memory and sensory function (P11, object recognition test), learning (P10, Skinner box) and histological evaluation of plasticity (P13 and P14) through dendritic spines and perineuronal nets assessment. The expected control values and their variabilities are presented together with the information on how to troubleshoot the most common issues related to each protocol. To sum up, this publication offers a comprehensive compilation of reliable protocols adapted to the rabbit model for neurodevelopmental assessment in toxicology.